Polymorphism of Ba2SiP4. Issue 3 (8th November 2019) - Haffner, Arthur; Weippert, Valentin; Johrendt, Dirk
Abstract : The three‐dimensional SiP4 network in the known phosphidosilicate Ba2 SiP4 ‐ tI 28 is analogous to β‐Cristobalite if oxygen is formally replaced by P–P dimers. Here we report a second polymorph Ba2 SiP4 ‐ oP 56 [ Pnma, a = 12.3710(4) Å, b = 14.6296(7) Å, c = 7.9783(3) Å; Z = 8] with chains of SiP4 tetrahedra connected by P–P bonds, reminiscent to the elusive fibrous SiO2 . Ba2 SiP4 is enantiotropic. The high temperature polymorph Ba2 SiP4 ‐ oP 56 transforms to the low‐temperature phase Ba2 SiP4 ‐ tI 28 at 650 °C and reconstructs to the high‐temperature modification at 1100 °C. DFT calculations predict an indirect optical bandgap of about 1.7 eV. Abstract :